DEVELOPMENT MATHEMATIC MODULE OF LINEAR EQUATION AND INEQUALITIES OF ONE VARIABLE MATERIAL FOR STUDENTS IN GRADE VII SMP/MTs - Melvinasari Melvinasari; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
This research is motivated by curriculum changes that require students to play a more active role in the learning process and the lack of mathematics teaching materials based on the curriculum of 2013, especially on linear equations and inequalities of one variable subject. This development research aims to develop teaching materials in the form of Mathematics Module for linear equation and inequality one variable subject for Grade VII Students of Junior High School (SMP / MTs) Based on Curriculum 2013. This research also aims to know the feasibility of modules developed based on material experts, media experts, and student responses. This study was conducted using the ADDIE development model. The development steps include Analysis, Design, Development, Implementation, and Evaluation. Mathematical Module Material for linear equations and inequalities one variable for grade VII students SMP / MTs is developed based on the 2013 curriculum. This product has gone through a revision phase based on suggestions and input from material experts and media experts. The results showed that the teaching materials of mathematics module material of linear equations and inequality one variable for grade vii students of SMP / MTs based on the curriculum 2013 have excelent quality, seen from the validity criteria. Based on the expert assessment of the material obtained an average score of 139 that meets the criteria very well, and based on the assessment of media experts obtained an average score of 129 that meets the criteria very well, based on student responses obtained an average score of 123.43 that meets the criteria very well. Based on the research result, the mathematics module matter of linear equation and inequality one variable for grade VII students of SMP/MTs based on curriculum 2013 is suitable for mathematics learning.